Współczesna demokracja a społeczeństwo obywatelskie na przykładzie Polski - Rachwał, Marcin (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
In order to function properly, a modern democracy needs a civic society, that is a society of individual, conscious subjects, who are active in the public realm. The absence of this component of democracy results in numerous problems, if only to mention low turnout in elections and referenda, thereby weakening the legitimacy of power and difficulties in the implementation of political decisions. Many authors emphasize the fact that the 1980s were a period of very intensive development in civic society in Poland which persuaded the authorities at the time to commence talks with the democratic opposition. The outcome of the talks of the Round Table, the elections in June 1991 and further events, was that a democratic political system was institutionalized in Poland. After several years of political transformation the issue of the weakness of Polish civic society was raised more and more frequently. Therefore, the question may be asked of what has happened to Polish society? A society that was once able to force the non-democratic authorities to make concessions after the turning point of 1989, has become less and less involved in public life. In trying to address this problem one needs to emphasize the fact that Polish civic society was revived at the time of the struggle against the socialist state. After the change of political system, the negative aftermath of the relations between state and citizens has produced certain difficulties. Consequently, new mutual relations need to be established between state and citizens, since a democratic system requires a functioning civic society that does not struggle against the state but rather colla orates with it. It takes time to develop such an organization of society, though.